Development of Hollow Fiber Membranes Suitable for Outside-In Filtration of Human Blood Plasma - David Ramada; Bente Adema; Mohamed Labib; Odyl ter Beek; Dimitrios Stamatialis (Membranes)
Hemodialysis (HD) is a critical treatment for patients with end-stage kidney disease (ESKD). The effectiveness of conventional dialyzers used there could be compromised during extended use due to limited blood compatibility of synthetic polymeric membranes and sub-optimal dialyzer design. In fact, blood flow in the hollow fiber (HF) membrane could trigger inflammatory responses and thrombus formation, leading to reduced filtration efficiency and limiting therapy duration, a consequence of flowing the patients’ blood through the lumen of each fiber while the dialysate passes along the inter-fiber space (IOF, inside-out filtration). This study investigates the development of HF membranes for “outside-in filtration” (OIF) in HD. In OIF, blood flows through the inter-fiber space while dialysate flows within the fiber lumens, reducing the risk of fiber clogging and potentially extending treatment duration. For the OIF mode, the membrane should have a blood-compatible outer selective layer in contact with the patient’s blood. We develop HFs for OIF via liquid-induced phase separation using PES/PVP (polyethersulphone/polyvinylpyrrolidone) blends. The fibers’ surface morphology (SEM, scanning electron microscopy), chemistry (ATR-FTIR—attenuated total reflection-Fourier transform infrared spectroscopy, XPS—X-ray photoelectron spectroscopy), transport properties, and uremic toxin removal from human plasma are evaluated and compared to commercial HFs. These membranes feature a smooth, hydrophilic outer layer, porous lumen, ultrafiltration coefficient of 13–34 mL m2 h−1 mmHg−1, adequate mechanical properties, low albumin leakage, and toxin removal performance on par with commercial membranes in IOF and OIF. They offer potential for more efficient long-term HD by reducing clogging and systemic anticoagulation needs and enhancing treatment time and toxin clearance.